Penetapan kadar flavonoid total ekstrak etanol buah asam kandis (Garcinia xanthochymus) dengan metode spektrofotometri Uv-Vis dan LCMS - Hanafis Sastra Winata; Hendri Faisal; Muhammad Andry; Nurul Aulia; Muhammad Amin Nasution; Ika Julianti Tambunan (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background: Kandis acid fruit (Garcinia xanthocymus Hook. f ex T. Anderson) is a plant of the Clusiase family with many species. Kandis acid fruit has various biological and pharmacological activities such as cytotoxic, anti-inflammatory, antimicrobial, antifungal and antioxidant. Purpose: To determine the content and total flavonoid content of tamarind kandis using quercetin as a reference standard. Method: This study used the TLC (Thin Layer Chromatography) method in qualitative analysis with the parameter Rf, then used the spectrophotometric method in the quantitative analysis with the parameter total flavonoid content (Value of mg QE/g sample) and the LCMS method (Liquid Chromatography Mass Spectrometry) with the parameter retention time (Rt). Result: Shows that tamarind kandis has an Rf value of 0.86 which states that tamarind kandis is positive for flavonoids with a reference standard of quercetin, total flavonoid content of 34.8364 mg QE/g sample with a standard deviation of 0.4355 and a percentage of 0.6967% and has five types of flavonoid compounds namely methyl dihydro quercetin, 1,5-Dihydroxy-3-methoxy xanthone, Afzelechin, Myricetin-3-O-ß-D-galactopiranoside, and Myricetin 7-glucoside. Methyl dihydro quercetin is the largest flavonoid with a composition of 49.57% with a retention time of 0.485 minutes. Conclusion: The identified total flavonoids have different types and levels